An evaluation of matrix training to teach college students piano notes and rhythms. Issue 3 (27th February 2020) - Langton, Emily K.; Miguel, Caio F.; Diaz, Jocelyn E.; Cordeiro, Maria Clara; Heinicke, Megan R.
Abstract : Twelve college students learned to tact the names of notes and rhythms and play them when presented with compound stimuli (visuals of notes and rhythms on a musical staff). In Experiment 1, we assessed generalization by presenting novel notes, rhythms, and compound stimuli not previously paired together. In the second experiment, we added a metronome that played at 60 beats per minute in all conditions for 3 out of 6 participants to ensure consistent tempo. Across both experiments, participants passed almost all posttests with the exception of tacting and playing in the presence of sound clips. Our data suggest that matrix training is an effective procedure to teach music skills to college students.